Portaria PGR/MPF nº 424, de 4 de julho de 2025 - Hindenburgo Chateaubriand Pereira Diniz Filho (DOU, Brasília, DF, 9 jul 2025. Seção 1, p. 133., 2025)
Revoga o art. 4º da Portaria PGR/MPF nº 413, de 30 de junho de 2025.
Keywords: 19 Outros assuntos